1997
DOI: 10.7164/antibiotics.50.1064
|View full text |Cite
|
Sign up to set email alerts
|

16-Methyloxazolomycin, a New Antimicrobial and Cytotoxic Substance Produced by a Streptomyces sp.

Abstract: Triene antibiotics containing /Mactone-y-lactam bicyclospiro and oxazole rings are unique metabolites produced by Streptomyces spp., such as oxazolomycins1'2) and curromycins.3'4)In the course of our continuing search for novel antimicrobial agents from microorganisms, an actinomycete strain Streptomyces sp. isolated from a soil sample collected in Taejon, Korea, was found to produce a new antibacterial 16-methyloxazolomycin (1). In this paper, we describe the production, isolation, structural elucidation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 7 publications
(3 reference statements)
0
31
0
Order By: Relevance
“…1) The distinctive structure consists of a highly unsaturated C-20 carbon chain with a dienyne moiety and methyl branches of biosynthetic interest. Only two examples of this type with a C-20 carbon skeleton are known other than 1, 1) although a series of related compounds that possess the right-half (C1-C9 moiety) of 1 have been discovered from actinomycetes, e.g., phthoxazolins (or inthomycins), [2][3][4][5] oxazolomycins, [6][7][8][9][10][11] and curromycins. 12,13) In our search for novel antifungal metabolites from marine organisms, 1 was rediscovered from an Okinawan marine sponge of Psammoclemma sp.…”
mentioning
confidence: 99%
“…1) The distinctive structure consists of a highly unsaturated C-20 carbon chain with a dienyne moiety and methyl branches of biosynthetic interest. Only two examples of this type with a C-20 carbon skeleton are known other than 1, 1) although a series of related compounds that possess the right-half (C1-C9 moiety) of 1 have been discovered from actinomycetes, e.g., phthoxazolins (or inthomycins), [2][3][4][5] oxazolomycins, [6][7][8][9][10][11] and curromycins. 12,13) In our search for novel antifungal metabolites from marine organisms, 1 was rediscovered from an Okinawan marine sponge of Psammoclemma sp.…”
mentioning
confidence: 99%
“…3 Curromycin A and curromycin B were formerly termed as triedimycin A and triedimycin B. 4 In 1997 16-methyloxazolomycin (5) was isolated as a product from Streptomyces sp. as another member of the oxazolomycin family.…”
Section: Discovery Of Oxazolomycinsmentioning
confidence: 99%
“…as another member of the oxazolomycin family. 5 Two novel oxazolomycins, specically oxazolomycin B (3) and oxazolomycin C (4) were reported in 1998 by Kanzaki et al as the products of Streptomyces albus JA3453. 6 Otani et al in 2000 reported isolation of KSM-2690 B (8) and KSM-2690 C (9) from the broth ltrate of Streptomyces strain KSM-2690 and they were classied as novel oxazolomycins.…”
Section: Discovery Of Oxazolomycinsmentioning
confidence: 99%
See 1 more Smart Citation
“…A search in AntiBase [61] using the above spectral data of compound 262 resulted in lajollamycin [394] as the sole known structure (Table 36). The identity with lajolamycin (262) [395] 16-methyloxazolomycin [396] (265), and triedimycin B6 (266) were previously isolated from bacteria. Lajollamycin (262) was isolated from the marine actinomycete Streptomyces nodosus (NPS007994); it is a potent antimicrobial agent against both against drug-sensitive and -resistant Gram-positive bacteria, as well as an in vitro inhibitor of B16-F10 tumor cells [394] .…”
Section: Polyisopropylenglycolmentioning
confidence: 99%